Effect of Packaging on Shelf-life and Lutein Content of Marigold (Tagetes erecta L.) Flowers - Pal, Sayani; Kumar Ghosh, Probir; Bhattacharjee, Paramita (Recent Patents on Biotechnology, 2016)
Background: African marigold (Tagetes erecta L.) flowers are highly valued for their ornamental appeal as well as medicinal properties. However, their short shelf lives cause high post-harvest loss and limit their export potential. The review of patents and research articles revealed that different types of packaging designs/materials have been successfully employed for extension of shelf lives of cut flowers. Objective: The current work focuses on designing of different packaging configurations and selection of best configuration for preservation of marigold cut flowers. Methods: Ten packaging configurations, composed of four different packaging materials i.e., low density polyethylene (LDPE), polyethylene terephthalate, glassine paper and cellophane paper, were designed. Each pack, consisting of 20 ± 1 g of marigold flowers along with non-packaged control set were stored at 23 ± 2°C, 80% R.H., in an environmental chamber and the flowers were evaluated for their sensory attributes, phytochemical characteristics and physicochemical parameters of senescence to determine their shelf lives. Results: Flowers packed in LDPE bag showed highest shelf life of 8 days with a lead of 4 days compared to control (shelf life - 4 days). This study also established for the first time the phenomenon of carotenogenesis in marigold cut flowers with significantly (P<0.01) higher production of lutein in LDPE packaged flowers. Conclusion: LDPE pack was the best design among the ten package designs, in preserving lutein content of marigold flowers and extending their shelf lives. This economically viable packaging can not only boost the export potential of this ornamental flower, but also allow utilization of nutraceutical potency of lutein.
Keywords: Packaging configurations